2021
DOI: 10.1111/1462-2920.15548
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent microbial community types driven by nearshore and seasonal processes in coastal Southern California

Abstract: A multitude of concurrent biological and physical processes contribute to microbial community turnover, especially in highly dynamic coastal environments. Characterizing what factors contribute most to shifts in microbial community structure and the specific organisms that correlate with changes in the products of photosynthesis improves our understanding of nearshore microbial ecosystem functions. We conducted high frequency sampling in nearshore Southern California in order to capture sub-weekly microbial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Monitoring programs that generate multi-disciplinary time-series datasets have been instrumental in detecting temporal patterns of change and seasonal shifts/cycles, alongside variability in environmental parameters and biological communities 6 , 7 . Furthermore, high-frequency sampling has allowed quantification of the impacts of short- and long-term stressors on coastal ecosystems specifically 8 10 and marine ecosystems in general 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring programs that generate multi-disciplinary time-series datasets have been instrumental in detecting temporal patterns of change and seasonal shifts/cycles, alongside variability in environmental parameters and biological communities 6 , 7 . Furthermore, high-frequency sampling has allowed quantification of the impacts of short- and long-term stressors on coastal ecosystems specifically 8 10 and marine ecosystems in general 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic placement algorithms require a reference tree, a corresponding reference multiple sequence alignment, and a collection of query sequences: the output is a set of assignments of the query sequences to branches of the tree (Matsen et al 2012 ). This tool has been recently used to finely characterize microbial communities in coastal marine (Wilson et al 2021 ) and freshwater (Iniesto et al 2021 ) environments. Moreover, it has been applied to profile the gut microbiota in toxic and non-toxic puffer fish species (Li et al 2020 ) and to assign taxonomy to the white shrimp Litopenaeus vannamei gut oligotypes allowing to study the link between the presence and abundance of pathogenic opportunistic Vibrio species and atypical mass mortality (López-Cortés et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria, archaea, and heterotrophic eukaryotes are particularly important for remineralizing bloom-derived organic matter (Buchan et al, 2014). Previous work has identified consistent taxonomic shifts in portions of the heterotrophic community in response to 'typical' sized blooms (Teeling et al, 2016;Wilson et al, 2021) and succession in the bacterial community has been observed following a HAB of Heterosigma akashiwo (Matcher et al, 2021). In particular, members of Flavobacteriales (Kirchman, 2002;Avci et al, 2020;Ferrer-Gonzalez et al, 2020;Matcher et al, 2021;Wilson et al, 2021) and Rhodobacterales Buchan et al, 2014) have both been shown to increase in response to phytoplankton-derived polysaccharides from variously sized blooms.…”
Section: Introductionmentioning
confidence: 95%